Analysis of Securities Offering Regulations on Securities Crowdfunding Services Maslahah Approach - Ulum, Kefi Miftachul (Studi Multidisipliner: Jurnal Kajian Keislaman, 2024)
The acceleration of the Digital Era began with the spread of the COVID-19 virus, which caused the national economy to grow 2.5% in 2020, or down 5% from 2019. The lockdown policy was a factor in the slow turnaround of the economy. Another impact is digitalization in all aspects, including the financing sector and the formation of rules to regulate financing. Financial technology is an instrument that is experiencing accelerated growth because it is based on the internet of things (IOT). With the birth of the concept of crowdfunding securities, which has become an alternative funding source for business actors such as MSMEs, Initially, MSME funding activities in the crowdfunding cycle were limited to equity based on POJK 37 of 2018, then the regulation developed into POJK 57 of 2020 and became POJK 16 of 2021. These regulatory changes changed the funding mechanism, which was initially equity-based and then developed to be based on sukuk and debt securities. These regulatory changes became the focus of research after examining the impact of these regulations on the funding of MSMEs and legal business entities in Indonesia. Mas}lah}ah theory became the knife in analyzing these regulations using normative legal research methodology as the research method and descriptive analysis as the analytical method. The use of this theory is based on the impact of existing regulatory developments, which have reached funding worth $1 trillion and contain 481 business units, with funding sources coming from 160,368 investors. This funding achievement is a challenge to carry out comprehensive supervision regarding the distribution and use of capital by service-provider companies and the Financial Services Authority by paying attention to the principles of GCG, CSR, and open disclosure to guarantee and protect the rights of parties participating in related funding.